A Wireless Charging System Based on the Interleaved Converter and Magnetic Integration - SUN Feng; TIAN Yuhong; DONG Henan; LI Ping; XIE Bing; LIU Yiqi (Journal of Harbin University of Science and Technology, 2023)
Steady outputs, high system efficiency and power density are significant for wireless charging systems.To meet the demand, this article introduces the two-cell interleaved Buck converter (IBC) to the wireless charging system (WCS). Combined with the closed-loop control, the constant current/constant voltage (CC/CV) outputs are realized by adjusting the IBC duty cycle.IBC can reduce the converter device stress, power losses, and current ripples, enhancing converter efficiency and avoiding the negative effects on load lifetime.In addition, the external power inductors are integrated with the coupler based on magnetic integration.Without affecting the power transfer, the LCC compensation inductor, IBC filter inductors are integrated with the transmitter and receiver at the same time, improving the system level. Finally, a prototype of 67.2 V/8 A verifies the WCS feasibility, realizing the CC/CV charging.